Developing and validating a scoring tool for identifying people who inject drugs at increased risk of hepatitis C virus infection. Issue 1 (4th January 2012) - Wand, Handan; Iversen, Jenny; Wilson, David; Topp, Libby; Maher, Lisa
Abstract : Objectives: To develop and validate a scoring tool based on demographic and injecting risk behaviours to identify those who require additional, non-routine serological screening for hepatitis C virus (HCV) by assessing their personal risk. Design: Cross-sectional and prospective cohorts. Setting: People who inject drugs (PWID) and attended Needle and Syringe Programs (NSP) in Australia during the period from 1998 to 2008. Participants: Cross-sectional data included 16 127 PWID who attended NSP in Australia. Prospective data included 215 HCV-negative PWID who were recruited through street-based outreach, methadone clinics in Australia. Primary and secondary outcome measures: HCV seroprevalence in the cross-sectional and HCV seroconversions in the prospective data sets. Results: Current study included 16 127 PWID who attended NSP in Australia. Type of drug last injected, frequency and duration of injecting, sharing needles and syringes or other injecting equipment and imprisonment history were associated with HCV infection in all age groups. Strong relationships between an individual's 'HCV score' and their risk of testing HCV antibody positive were observed. An estimated 78% (95% CI 75% to 81%), 82% (95% CI 80% to 84%), 80% (95% CI 78% to 82%) and 80% (95% CI 77% to 82%) of HCV infections across the age groups (<25, 25–29, 30–39 and ≥40 years) would be avoided if participants in the upper four quintiles of HCV scores fell instead into the lowest quintile. Conclusions: Knowledge of HCV status has important implications for public health and care and treatment. Risk assessment strategies may assist in alerting PWID who are at increased risk of HCV infection to present for testing.